The global village of coeliac disease - Catassi, Carlo; Fasano, Alessio; Corazza, Gino Roberto (AIC Italian Coeliac Society, 2005)
A collection of works that focus on various aspects of coeliac disease. Intended for professional public.
Perspectives on coeliac disease ; Volume II
Keywords: celiakie; gastroenterologie; alergologie a imunologie; Celiac Disease